2010
DOI: 10.1038/sj.bjc.6605537
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of stathmin1 in the diffuse type of gastric cancer and its roles in proliferation and migration of gastric cancer cells

Abstract: BACKGROUND: Stathmin1 is a microtubule-regulating protein that has an important role in the assembly and disassembly of the mitotic spindle. The roles of stathmin1 in carcinogenesis of various cancers, including prostate and breast cancer, have been explored. However, its expression and roles in gastric cancer have not yet been described. METHODS: Stathmin1 expression in paraffin-embedded tissue sections from 226 patients was analysed by immunohistochemistry. Roles of stathmin1 were studied using a specific sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 27 publications
8
74
1
1
Order By: Relevance
“…STMN was found extensively studied in relation to the cancer progression process (27,28) and in many studies directly linked to prostate cancer (29,30). STMN in our study was found downregulated multiple times (0.829, 0.829 and 0.783) as seen in Table I.…”
Section: Identification Of Differentially Expressed Proteins Upon Pdesupporting
confidence: 66%
“…STMN was found extensively studied in relation to the cancer progression process (27,28) and in many studies directly linked to prostate cancer (29,30). STMN in our study was found downregulated multiple times (0.829, 0.829 and 0.783) as seen in Table I.…”
Section: Identification Of Differentially Expressed Proteins Upon Pdesupporting
confidence: 66%
“…Stathmin1 is a microtubule-regulating protein that has an important role in the assembly and disassembly of the mitotic spindle. It has been shown to be involved in carcinogenesis, invasion, and metastasis of various cancers, including prostate, hepatocellular, and breast cancers (34,35,45,46). Since the cytotoxicity of ara-C is cell cyclespecific, stathmin1 could potentially affect the action of ara-C on the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…associated or cell cycle-regulating protein (34,35), it could be involved in mechanisms of resistance to the cell cycle-specific agent ara-C.…”
Section: Proteome Analysis Of Cem/ara-c Cellsmentioning
confidence: 99%
“…2 In addition to its role in mitosis and cell cycle progression, STMN1 is involved in a wide variety of human cancers, including gastric cancer, nasopharyngeal carcinoma, colorectal cancer, and endometrial carcinoma, etc. [3][4][5][6] For example, Kang et al 7 showed that STMN1 was upregulated in gastric cancer cell lines and primary gastric adenocarcinomas.…”
mentioning
confidence: 99%